Goldfish varieties and genetics : - Smartt, Joseph (Blackwell Science, 2001)
Goldfish Varieties and Genetics covers all major aspects relating to goldfish breeding and genetics in a readable and user-friendly style. An account is presented of the domestication and evolution of the goldfish, including comprehensive details of the relevant genetic and biological principles involved in the development strategies and production of new varieties. The book also covers the subject of goldfish appreciation and the international significance of goldfish shows and show standards. The book concludes with an exciting forward look at the potential evolutionary future for the goldfish.